Air pollution exposure during pregnancy among rural Ugandan women - Mahlaba, Harmony Boiketlo (Department of Public Health and Family Medicine, 2023)
Introduction: Air pollution monitoring of hazardous pollutants such as CO (Carbon Monoxide) and PM (Particulate Matter) are important for assessing whether air pollution thresholds are not exceeded in the environment. There is sparce data that has been collected in the African region for air pollution monitoring. In this study PM and CO are measured. Air pollution in pregnancy is associated with poor lung function in infants, in later life. The overall aim of this dissertation is to investigate air pollution exposure during pregnancy among rural Ugandan women. Methods: This mini-dissertation covers two components; the research protocol (Part A) and a manuscript section (Part B). We measured the CO and PM 2.5 levels in the study location of the Kyamulibwa Health Demographic Surveillance Site (HDSS), with a total population size of 22,000. Our study population were pregnant women. Household energy use was measured using personal monitoring tools. The Dylos tool was used to measure PM 2.5 in the households, while the Lascar tool was used to measure CO once a week at two different points at the HDSS. Boxplots were used to compare the relationship between air pollution exposures (CO and PM 2.5) and respiratory symptoms. Boxplots were further used to compare the relationship between air pollution exposure and infant birth weight. Furthermore, logistic regression models were used to show associations between air pollution exposure levels and infant birth weight as well as respiratory symptoms respectively. Results: The boxplots and regression models showing the relationship between air pollution exposure and respiratory symptoms suggest that mothers who presented no respiratory symptoms had lower levels of air pollution exposure compared to mothers who presented one or more symptoms. The boxplots and regression models also showed that air pollution exposure may not be a factor in low birthweight. Infants with low birth weight had lower air pollution exposure compared to infants with normal and high birth weight. Conclusion: Although it is evident through the results that there is a relationship between air pollution exposure and respiratory symptoms, further research is necessary to understand context specific ways in which exposure to air pollution can be reduced in both households and the general outside environment.